PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA PASAREAN KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Yunengsih, Herni (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
This Community Service aims to increase knowledge and skills in planning, compiling and managing Islamic finance for the Pasarean Village Community, Pamijahan District, Bogor Regency. The problem faced is the first, limited knowledge of sharia-based financial planning. Second, the lack of skills and ability to prepare budgets for sharia-based financial management. The solutions to these problems include: first, training to increase knowledge about sharia financial planning. Second, training in preparing an ideal budget. It is hoped that this solution will be able to plan and compile budgets for Islamic financial management so that they do not have a lifestyle with the desire to follow an emerging or developing trend that can lead to hedonism and other detrimental characteristics. The output of this activity is an increase in knowledge and an increase in skills in preparing the budget which shows the enthusiasm to immediately implement sharia family financial planning.